Uncomplicated moderate coronary artery dissections after balloon angioplasty: good outcome without stenting. Issue 2 (1st August 2001) - Albertal, M; Van Langenhove, G; Regar, E; Kay, I P; Foley, D; Sianos, G; Kozuma, K; Beijsterveldt, T; Carlier, S G; Belardi, J A; Boersma, E; Sousa, J E; et al.
Abstract : OBJECTIVE: To study the relation between moderate coronary dissections, coronary flow velocity reserve (CFVR), and long term outcome. METHODS: 523 patients undergoing balloon angioplasty and sequential intracoronary Doppler measurements were examined as part of the DEBATE II trial (Doppler endpoints balloon angioplasty trial Europe). After successful balloon angioplasty, patients were randomised to stenting or no further treatment. Dissections were graded at the core laboratory by two observers and divided into four categories: none, mild (type A-B), moderate (type C), severe (types D to F). Patients with severe dissections (n = 128) or without available reference vessel CFVR (n = 139) were excluded. The remaining 256 patients were divided into two groups according to the presence (group A, n = 45) or absence (group B, n = 211) of moderate dissection. RESULTS: Following balloon angioplasty, there was no difference in CFVR between the two groups. At 12 months follow up, a higher rate of major adverse cardiac events was observed overall in group A than in group B (10 (22%) v 23 (11%), p = 0.041). However, the risk of major adverse events was similar in the subgroups receiving balloon angioplasty (group A, 6 (19%) v group B, 16 (16%), NS). Among group A patients, the adverse events risk was greater in those randomised to stenting (odds ratios 6.603 v 1.197, p = 0.046), whereas there was no difference in risk if the group was analysed according to whether the CFVR was < 2.5 or ⩾ 2.5 after balloon angioplasty. CONCLUSIONS: Moderate dissections left untreated result in no increased risk of major adverse cardiac events. Additional stenting does not improve the long term outcome.